Lead toxicity and phytoextraction potential of Acacia auriculiformis A. Cunn. ex Benth. to remediate lead-polluted soil - Abderrahmane, Zerkout (2020)
Phytoremediation takes a longer time to accomplish than other treatment. Phytoextraction with Acacia auriculiformis, also known as Auri, Earleaf acacia, Earpod wattle, Northern black wattle, Papuan wattle and Tan wattle, has not been reported previously even though it is a fast-growing species and able to grow well in very poor soil. This study was conducted to determine the impact of lead (Pb) on A. auriculiformis seed germination, the influence of Pb on A. auriculiformis growth, the capability of A. auriculiformis to remove Pb from the soil and the effect of NPK fertilizer on the speed of growth as well as the absorption of Pb from the soil. Seeds were exposed to Pb by soaked it in different Pb concentrations from 0 to 4 g/L (interval of 0.5 g/L). The evaluation of Pb impact on A. auriculiformis seed germination and early radicle development was conducted based on germination percentage (GP), germination index (GI), mean germination time (MGT), seedling vigour index (SVI), relative injury rate (RIR) and histological observation on seed embryo development. Biochemical response of A. auriculiformis seeds towards Pb stress was assessed by determining the phenolic compounds, malondialdehyde and starch content. Physical growth parameters such as shoot height, leaves number, basal diameter and root length were measured. Several physiological parameters including net photosynthesis, total chlorophylls, internal CO2 concentration, transpiration rate, the relative water content (RWC) and water use efficiency (WUE) were also measured. The enzymatic respond to Pb toxicity was assessed by measuring the catalase activity. While the concentration of Pb concentration in the soil and plant part was determined using Inductively coupled plasma atomic emission spectroscopy (ICP AES). The bioconcentration factor (BCF) and the translocation factor (TF) were calculated to assess A. auriculiformis phytoremediation potential. The effect of the NPK fertilizer with a ratio of 1:1:1on A. auriculiformis growth was assesed by measuring the same morphological and physiological parameters as ststed previously. All the collected data were analysed using one way analysis of variance (ANOVA). via IBM SPSS Statistic Version 25 software. The triplicates data were presented as mean ± standard deviation based on the Tukey’s HSD test. Study reveals that Pb toxicity has does not affect A. auriculiformis seeds germination up to 1.5 g/L. Increasing the concentration of Pb up to 3.5 g/L led to a reduction in GP and GI while an increment in the MGT caused the germination to be delayed by almost 10 days. The SVI and RIR results indicated that Pb has also affected seeds strength and ability to repair the damage. High starch accumulation in A. auriculiformis seeds caused a reduction in nutrient availability which adversely reduces the embryo development. The assessment of growth parameters also showed that Pb did not affect A. auriculiformis grown in 1 g/kg Pb-treated soil. The plant grown in 1 g/kg Pb-treated soil showed a 12% decrement in WUE and RWC, but no significant difference was recorded between 1 g/kg, 2 g/kg and 3 g/kg Pb-treated soil. This is coherence with the proline and catalase responses. Catalase findings showed that Pb caused a significant overproduction of the CAT enzyme in A. auriculiformis. Thus, proving that A. auriculiformis has a good antioxidant defence system to overcome the Pb stress. Analysis of BCF and TF values showed that values for A. auriculiformis grown in 1 g/kg Pb-treated soil were 3.5 and 1.28, respectively. The BCF and TF results indicated that A. auriculiformis could be used as a phytoextractor at Pb concentration of 1 g/kg and as phytostabilizer at 2 g/kg. The NPK fertilizer application enhanced A. auriculiformis morphological parameters by 55% and an increment was observed in net photosynthesis, total chlorophylls, the transpiration rate, the internal CO2 concentration and RWC. Proline accumulation was significantly reduced ranging from 15% to 50% depend on the Pb concentration in the soil. However, no significant difference between the CAT enzyme production in the presence and the absence of the NPK fertilizer. Data on BCF and the TF for A. auriculiformis treated with the NPK fertilizer showed lower value compared to without NPK. Thus, indicated that in the presence of NPK, A. auriculiformis is unable to absorb and translocate a significant amount of Pb from the soil to the different parts of the plant. Based on the all data and tolerance index, A. auriculiformis has the potential to be used as a phytoremediation agent for Pb. Combination of its ability to grow in unfertile soil and resistance to Pb up to 2 g/kg does give it some advantage as phytoremediation agent.